Pengaruh Penerapan Sistem Akuntansi Keuangan Daerah Dan Sistem Pengendalian Internal Terhadap Kualitas Laporan Keuangan Pemerintah Daerah Dengan Kompotensi Sumber Daya Manusia Sebagai Variabel Moderasi (Study Empiris Pada Kabupaten Waropen) - Watopa, Moses; Kambu, Arius; Ngutra, Risky Novan (KEUDA (Jurnal Kajian Ekonomi dan Keuangan Daerah), 2023)
The purpose of this study was to analyze: (1) analyze the effect of the Regional Financial Accounting System Implementation on the Quality of Financial Statements of the local government of Waropen Regency; (2) Analyze the effect of the Internal Control System on the Quality of Financial Statements of the local government of Waropen Regency; (3) Analyze the effect of the implementation of the Regional Financial Accounting System on the Quality of Financial Statements of the local government of Waropen Regency with Human Resource Competence as a moderation variable; (4) Analyze the effect of the Internal Control System on the Quality of Financial Statements of the local government of Waropen Regency with Human Resource Competence as a moderation variable. This research was conducted within the scope of Waropen Regency government. The sampling technique is carried out using pusposive sampling techniques. The type of research data used in this study is a type of quantitative data. The data analysis used in this study was Moderated Regression Analysis (MRA) which was carried out using SPSS software. The results showed that: (1) the significance value of the variable Application of the Regional Financial Accounting System was 0.048 > 0.05 so that it could be concluded that the Regional Financial Accounting System did not affect the Quality of Local Government Financial Statements; (2) the significance value of the Internal Control System variable is 0.043 > 0.05 so that it can be concluded that the Internal Control System does not affect the Quality of Local Government Financial Statements; (3) the significance value of the interaction variable between the Application of the Regional Financial Accounting System and the Competence of Human Resources of 0.299 > 0.05 so that it can be concluded that the Competence of Human Resources is unable to moderate the effect of the Application of the Regional Financial Accounting System on the Quality of Local Government Financial Statements; (4) the significance value of the interaction variable between the Internal Control System and Human Resource Competence is 0.063 > 0.05 so that it can be concluded that Human Resource Competence is unable to moderate the influence of the Internal Control System on the Quality of Local Government Financial Statements.